2017
DOI: 10.5812/jjm.13571
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Genotyping of Methicillin-Resistant and - Susceptible Staphylococcus aureus Strains Isolated from Patients in a University Hospital, Isfahan, Iran

Abstract: Background: Staphylococcus aureus is one of the major causes of community-and hospital-acquired infections, with methicillinresistant strains showing the highest rates of morbidity and mortality. In our previous experiment, isolates, which were also used in the present study, were assessed using multilocus sequence typing (MLST). The sequence types (STs) were determined and documented in the corresponding database. Objectives: In the current study, the isolates were subjected to genotyping with coagulase, SCCm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 28 publications
2
11
0
Order By: Relevance
“…In a study conducted by Goudarzi et al [24] in the city of Tehran, ST22 has been documented as the third most commonly detected MRSA clone though the mentioned strains belonged to ST22-SCCmec IV in comparison to our MRSA ST22 which was ST22-SCCmec V. These ndings highlight the importance of using several typing methods simultaneously to achieve better analysis. In previous studies of MRSA and MSSA strains in the cities of Isfahan and Tehran the majority of MRSA isolates belonged to ST239 [25].…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…In a study conducted by Goudarzi et al [24] in the city of Tehran, ST22 has been documented as the third most commonly detected MRSA clone though the mentioned strains belonged to ST22-SCCmec IV in comparison to our MRSA ST22 which was ST22-SCCmec V. These ndings highlight the importance of using several typing methods simultaneously to achieve better analysis. In previous studies of MRSA and MSSA strains in the cities of Isfahan and Tehran the majority of MRSA isolates belonged to ST239 [25].…”
Section: Discussionmentioning
confidence: 86%
“…In the present study, in contrast SCCmec type V was the most prevalent SCCmec type identi ed among our clinical isolates of MRSA. However recent studies conducted in Armenia and Iran, SCCmec types V and IV were the most types that identi ed among MRSA isolates from hospitals respectively [13,25] Also in a study by Hallin et al [26] in Belgium, most clinical MRSA strains belonged to SCCmec types IV. These results could con rm the rotation of clones between community and hospital.…”
Section: Discussionmentioning
confidence: 94%
“…In the present study, in contrast SCCmec type V was the most prevalent SCCmec type identified among our clinical isolates of MRSA. However recent studies conducted in Armenia and Iran, SCCmec types V and IV were the most types that identified among MRSA isolates from hospitals respectively [8,25] Also in a study by Hallin et al [26] in Belgium, most clinical MRSA strains were belonged to SCCmec types IV. These results could confirm the rotation of clones between community and hospital.…”
Section: Discussionmentioning
confidence: 92%
“…These findings highlight the importance of using several typing methods simultaneously to achieve better analysis. In previous studies of MRSA and MSSA strains in the cities of Isfahan and Tehran the majority of MRSA isolates belonged to ST239 [25]. The high prevalence of ST239 has been documented from many Asian countries especially India, Pakistan, Vietnam, Thailand, Taiwan, China, Sri Lanka, and Singapore [27].…”
Section: Discussionmentioning
confidence: 93%
“…MRSA is one of the most prevalent pathogens in the world that is responsible for a wide range of nosocomial infections. 5,6 Studies have shown that contaminated medical staff (including doctors, nurses, and even service personnel in departments) are common sources of antibiotic-resistant Staphylococcus aureus epidemics in the hospital. MRSA which are separated from hospitals are called Healthcare-associated MRSA (HA-MRSA), and those which are separated from the community are named Community-Acquired MRSA (CA-MRSA).…”
Section: Introductionmentioning
confidence: 99%